Role of Electrolytes in the Stability and Safety of Lithium Titanate-Based Batteries - Ghosh, Arunabh; Ghamouss, Fouad (Frontiers in Materials, 2020)
Lithium titanate (Li4Ti5O12, LTO) has emerged as an alternative anode material for rechargeable lithium ion (Li+) batteries with the potential for long cycle life, superior safety, better low-temperature performance, and higher power density compared to their graphite-based counterparts. LTO, being a “zero-strain” material, shows almost no volume change (<1%) during lithium ion insertion/extraction and hence offers excellent cycling stability (over 20,000 cycles). LTO anodes were popular initially on the belief that the anode electrolyte interface would be free of any solid electrolyte interphase (SEI) layer; however, this was found not to be the case. Rather, recent studies have reported different types of deposits and layer formations on the surface of LTO electrodes, and therefore this topic has received significant attention in recent years and has emerged as an important research direction. However, these anodes, being very active catalysts, are prone to undesirable reactions with electrolytes and problems such as gas evolution, and associated swelling of the battery pack may occur. Also, the electrolytes have been found to be one of the primary sources of problems, given that the electrolytes may react with both the anode and cathode, creating serious stability and safety concerns. The presence of moisture within the battery system, decomposition of the electrolyte solvents and solutes, and high catalytic activity of the anode are among the possible reasons behind the instability of LTO-based batteries. Development of an appropriate chemical composition for the electrolyte and/or modification of the electrode/electrolyte interface may overcome these issues.